Earnings inequality in India: has the rise of caste and religion based politics in India had an impact? - Sumon Kumar Bhaumik; Manisha Chakrabarty (Institute for the Study of Labor (IZA), 2006)
Since 1989, there has been a sharp increase in the role of caste and religion in determining political fortunes at both state and federal levels in India. As a consequence, significant inter-caste and inter-religion differences in earnings have the potential to stall the process of economic reforms. Yet, the patterns and determinants of such differences remain unexplored. We address this lacuna in the literature, and explore the determinants of the differences in inter-caste and inter-religion earnings in India during the 1987-99 period, using the 43rd and 55th rounds of National Sample Survey (NSS). Our results suggest that (a) earnings differences between upper castes and SC/ST have declined between 1987 and 1999, (b) over the same period, earnings differences between Muslims and non-Muslims have increased, to the detriment of the former, and (c) inter-caste and inter-religion differences in earnings can be explained largely by corresponding differences in educational endowment and returns on age (and, hence, experience). However, differences in returns on education do not explain inter-caste and inter-religion earnings differences to a great extent.
Keywords: O15; O17; 330; inequality; caste; religion; India; Einkommensverteilung; Soziale Schicht; Religion; Indien; Soziale Ungleichheit